2015
DOI: 10.1161/atvbaha.115.305655
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor Protects the Heart Against Reperfusion Injury and Improves Remodeling After Myocardial Infarction

Abstract: Objective-In addition to P2Y 12 receptor antagonism, ticagrelor inhibits adenosine cell uptake. Prior data show that 7-day pretreatment with ticagrelor limits infarct size. We explored the acute effects of ticagrelor and clopidogrel on infarct size and potential long-term effects on heart function. Approach and Results-Rats underwent 30-minute ischemia per 24-hour reperfusion. (1) Ticagrelor (10 or 30 mg/kg) or clopidogrel (12.5 mg/kg) was given via intraperitoneal injection 5 minutes before reperfusion. (2) R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
113
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 58 publications
9
113
1
Order By: Relevance
“…The observed cardioprotective results represented by reduced infarct area and myocardial proinflammatory cytokine levels from our study are in line with previous finding showing that a single acute dose of ticagrelor via intraperitoneal injection (30 mg kg −1 ) 5 min before reperfusion significantly reduced infarct size and reduced the proinflammatory cytokine levels in a rat ischaemia/reperfusion model 15. It is noted that IA/AAR ratio tended to be lower at 24 h as compared to 3 days and 7 days in the placebo‐treated rats ( P  > 0.05).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The observed cardioprotective results represented by reduced infarct area and myocardial proinflammatory cytokine levels from our study are in line with previous finding showing that a single acute dose of ticagrelor via intraperitoneal injection (30 mg kg −1 ) 5 min before reperfusion significantly reduced infarct size and reduced the proinflammatory cytokine levels in a rat ischaemia/reperfusion model 15. It is noted that IA/AAR ratio tended to be lower at 24 h as compared to 3 days and 7 days in the placebo‐treated rats ( P  > 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…Multiple mechanisms have been indicated for the beneficial effects of ticagrelor in attenuating ischaemic insult, including increasing myocardial adenosine levels, augmenting the phosphorylation of the pro‐survival kinases Akt and ERK 1/2 and endothelial NO synthase 15 as well as inhibiting glandular transporter (ENT‐1) on erythrocytes glycoside reuptake, strengthening of the local adenosine response, and vasodilation 14, 27, 33. Previous studies also suggested that the cardioprotective effects of ticagrelor was independent of its role in inhibition of platelet aggregation, as the cardioprotective effects were not observed post clopidogrel application 14, 15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides its antiplatelet effect, ticagrelor has a pleiotropic action and it increases plasma adenosine concentration by reducing recapturing of adenosine by red blood cells [32]. Plasma adenosine facilitates arterial vasodilatation and may decrease injury caused by reperfusion [33,34]. It has been reported that ticagrelor prescription before reper fusion, after 4 weeks of antiplatelet treatment, improved animal (a rat) heart function [34].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma adenosine facilitates arterial vasodilatation and may decrease injury caused by reperfusion [33,34]. It has been reported that ticagrelor prescription before reper fusion, after 4 weeks of antiplatelet treatment, improved animal (a rat) heart function [34]. Compared with clopidogrel, ticagrelor is a more effective drug for decreasing platelet aggregation and the prevention of arterial thrombosis, such as definite stent thrombosis; this is because it has a more beneficial mechanism of action than clopidogrel [29], and it does not require metabolic activation.…”
Section: Discussionmentioning
confidence: 99%